Phytochemical and Pharmacological Evaluation of Fruits of Elaeocarpus Serratus for Antiurolithiatic Activity: an in Vitro Study - Rochana Maitra (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Medicinal plants are highly esteemed all over the world as a rich source of therapeutic agents for the prevention and treatment of various diseases. Since ages, herbs are being used for treating different ailments in different parts of world by different communities. Objective The present research work involves the evaluation of the pharmacognostical, phytochemical and in vitro antiurolithiatic activity of Elaeocarpus serratus fruit extract. Method The aqueous extract of Elaeocarpus serratus was prepared and phytochemical analysis indicated the presence of carbohydrate, phytosterols, tannins and phenolics. The semi-permeable membranes of eggs were used as dissolution bags. The spectrophotometric analysis has given good dissolution of calcium. Calcium oxalate was released 53.12% and 41.59% in case of standard and test respectively whereas calcium phosphate was released 55.72% and 32.06% for the standard and tests respectively. Conclusion So, it can be concluded that the extract of Elaeocarpus serratus has proved capability to dissolve calcium which may be helpful in removal of stone forming elements in urinary tract. Cystone, the standard drug has shown better demineralization for calcium phosphate as secondary for stone forming in urinary tract when compared to the extract of Elaeocarpus serratus.